Research Anthology on Business Aspects of Cybersecurity - Management Association, Information Resources (IGI Global, 2021)
Cybersecurity is vital for all businesses, regardless of sector. With constant threats and potential online dangers, businesses must remain aware of the current research and information available to them in order to protect themselves and their employees. Maintaining tight cybersecurity can be difficult for businesses as there are so many moving parts to contend with, but remaining vigilant and having protective measures and training in place is essential for a successful company. The Research Anthology on Business Aspects of Cybersecurity considers all emerging aspects of cybersecurity in the.